APPLICATION OF THE SHANNON AND WEAVER MODEL TO REDUCE MESSAGE DISTORTION IN SECURING THE 2024 DELI SERDANG ELECTION: PENERAPAN MODEL SHANNON AND WEAVER UNTUK MENGURANGI DISTORSI PESAN DALAM PENGAMANAN PEMILU 2024 DELI SERDANG - Syahputra, Romi; Kholil, Syukur (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The security operations for the 2024 election in Deli Serdang face significant communication challenges that risk causing message distortion, potentially undermining coordination between security personnel and the public. To address this issue, this study applies the Shannon and Weaver communication model as a framework to identify factors contributing to noise in information exchange on the ground. The research focuses on how the model’s elements—such as sender, communication channels, and receiver—can interact more effectively to minimize misunderstandings. Using a descriptive qualitative approach, data were gathered through in-depth interviews with security personnel and document analysis. Findings reveal that employing the Shannon and Weaver model aids in identifying vulnerable points that cause noise, such as message inconsistencies and limited communication media. By improving feedback mechanisms and minimizing sources of interference, coordination in election security can be substantially enhanced. This study concludes that understanding the principles of communication models is essential to ensuring message clarity and bolstering security responsiveness during election operations.